PENCEGAHAN BULLYING DAN DISKRIMINASI MELALUI PELATIHAN TEKNIK BELADIRI PRAKTIS - Nova Liana; Aridhotul Haqiyah (Universitas Islam 45 Bekasi, 2022)
The COVID-19 pandemic has hampered community activities in various fields, such as the economy, finance, education and health sectors. Based on the results of observations that have been made, there is still a lack of community knowledge about how to protect themselves from crimes and violence experienced, both on the road and at home. In addition, at this time there are also more and more crimes and violence against children, one of which is bullying and discrimination. This paper intends to increase knowledge, awareness, and public awareness of acts of bullying and discrimination carried out in RW 007, Kelapa Dua Wetan Village, Ciracas District, East Jakarta. The program of activities held was,